О роли скандинавских орфографических работ XVI–XVIII вв. в истории языкознания - Воронкова, Г.В. (Kalbotyra, 1979)
The article, which is a short critical survey of linguistic investigations of the 16th–18th centuries, shows the part played by orphographical reforms in the history of phonology. These reforms are an attempt to create new graphic-phonological systems.